Analisis makro ekonomi Indonesia pendekatan IS-LM - Imamuddin Yuliadi (Economic Journal of Emerging Markets, 2001)
A research of Indonesia's economy by IS-LM analysis to determine general equilibrium both in money market and goods market based on thought to know now for the capability of national economy in raising economic mobility that is showed by some macro economic indicators.